2021
DOI: 10.1038/s41598-021-86657-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined laser-based X-ray fluorescence and particle-induced X-ray emission for versatile multi-element analysis

Abstract: Particle and radiation sources are widely employed in manifold applications. In the last decades, the upcoming of versatile, energetic, high-brilliance laser-based sources, as produced by intense laser–matter interactions, has introduced utilization of these sources in diverse areas, given their potential to complement or even outperform existing techniques. In this paper, we show that the interaction of an intense laser with a solid target produces a versatile, non-destructive, fast analysis technique that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…The experimental setup and a picture of it are shown respectively in figures 1(A) and (B). The setup is similar to the one used in Puyuelo-Valdes et al [12] in which it was demonstrated that ultra-intense laser-matter interaction produces a versatile, non-destructive, fast analysis technique that allows to switch from laser-driven PIXE to laser-driven XRF, or to apply both techniques simultaneously, by simply varying the atomic number of the proton source target. This technique was named laser-based XPIF.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental setup and a picture of it are shown respectively in figures 1(A) and (B). The setup is similar to the one used in Puyuelo-Valdes et al [12] in which it was demonstrated that ultra-intense laser-matter interaction produces a versatile, non-destructive, fast analysis technique that allows to switch from laser-driven PIXE to laser-driven XRF, or to apply both techniques simultaneously, by simply varying the atomic number of the proton source target. This technique was named laser-based XPIF.…”
Section: Methodsmentioning
confidence: 99%
“…where N K α,β is the number of x-rays of the source (N K α = 4.3 ± 1.1 × 10 10 and N K β = 0.6 ± 0.2 × 10 10 photons sr −1 ) [12], σ i is the XRF cross section for production of K α radiation of the element i tabulated in the work of del Río et al [17], μ 1 and μ 2 are respectively the compound x-ray mass attenuation coefficient at the source energy (hν K α ) and at the emission energy of the K α line i in the sample, ρ is the density of the sample and t is the material thickness. The coefficient T(hν) in equations (2b) and (2c) accounts for the attenuation of the incoming x-rays and the emitted x-rays.…”
Section: Photon Yield Obtained By Xrfmentioning
confidence: 99%
See 1 more Smart Citation
“…So recently, the laser-induced X-ray uorescence measurement of artworks and cultural heritage has been reported. [9][10][11] Artworks and cultural heritage are often plated or painted over, so it is important to distinguish the information of material surface and interior; however, it is di cult to distinguish them owing to conventional X-ray tubes emitting monochromatic light, which have a larger penetration depth with several millimeters. So various experimental methods have been proposed for analyzing the interior of multi-layer materials.…”
Section: Introductionmentioning
confidence: 99%
“…[17] In contrast to conventional monochromatic X-ray sources, particles generated by laser plasma can be used to analyze only the surface of a material. For this purpose, X-ray uorescence using the laser-induced particle-induced X-ray emission (PIXE) method has been reported, [10] and the quantitative measurement was also studied in the same experimental environment. [18] Meanwhile, a high-power laser source with a peak intensity of 10 18 W/cm 2 or more is required for proton emission.…”
Section: Introductionmentioning
confidence: 99%